Study of the Effect of Wind Flow around the Ruin of a Fortified Tower Variously Covered by a Flat Roof: Analysis of the Extreme Values of Exterior Pressure and Surface Friction Coefficients - Poliak Martin; Franek Michal; Gregorová Jana (Slovak Journal of Civil Engineering)
An analysis of the effect of the covering of a ruin by a flat roof of various sizes and positions is presented. The ruin has almost cube-like proportions, with an open roof plane and an open destroyed corner. The coverage of the ruin by a roof is viewed as protection against wind and its associated destructive mechanisms. The effect of the wind flow is illustrated by the minimum and maximum values of the external pressure and the skin friction coefficients. Taking the changes of these values into account, the degree of protection of the ruin by the flat roof alternatives is estimated, and the optimal alternative for the coverage is discussed. Simulations of the wind study were conducted using the Fluent by Ansys, computational fluid dynamics software, 3D Time Steady Reynolds-Averaged Navier-Stokes equations, and the Shear Stress Transport k-ω turbulence model.